Policy Analysis in Mexico - Dussauge-Laguna, Mauricio I.; Mendez, Jose Luis (Book collections on Project MUSE., 2017)
This work provides a detailed examination of the practice of policy analysis in Mexico. It studies how public institutions and other non-state actors gather and review information and ponder options in the process of making (or trying to influence) policy decisions. Its chapters also offer explanations that are helpful for understanding how and why policy analysis activities vary across settings, and why this intellectual activity has made significant progress but is still far from being fully established in the country.